Decent employment and subjectivity in the workplace: notes for an agenda of labor policies in citizenship terms - Ferrari, Liliana Edith (2009)
Taking back the contemporary problems of work in terms of their actors, the aspects in which labor psychology can produce contributions and reflections are examined. The problem of diagnosis as well as that of understanding and elucidation of the limits and scope that employment policies can contain as proposals of palliative designs for processes not strictly linked to the psycho-social aspects of work, is assessed from the standpoint of decent employment.